How humans adapt to hot climates learned from the recent research on tropical indigenes - Tochihara, Yutaka; Wakabayashi, Hitoshi; Lee, Joo‑Young; Wijayanto, Titis; Hashiguchi, Nobuko; Saat, Mohamed (BioMed Central Ltd, 2022)
This review mainly aimed to introduce the findings of research projects comparing the responses of tropical and temperate indigenes to heat. From a questionnaire survey on thermal sensation and comfort of Indonesians and Japanese, we found that the thermal descriptor “cool” in tropical indigenes connotes a thermally comfortable feeling, suggesting that linguistic heat acclimatization exists on a cognitive level. Ten male students born and raised in Malaysia were invited to Fukuoka, Japan, and compared their responses with 10 Japanese male students with matched physical fitness and morphological characteristics. Cutaneous thermal sensitivity: The sensitivities were measured at 28 °C. The forehead warm sensitivity was significantly blunted in Malaysians. The less sensitivity to the warmth of tropical indigenes is advantageous in respect to withstanding heat stress with less discomfort and a greater ability to work in hot climates. Passive heat stress: Thermoregulatory responses, especially sweating, were investigated, during the lower leg hot bathing (42 °C for 60 min). The rectal temperature at rest was higher in Malaysians and increased smaller during immersion. There was no significant difference in the total amount of sweating between the two groups, while the local sweating on the forehead and thighs was lesser in Malaysians, suggesting distribution of sweating was different from Japanese. Exercise: Malaysian showed a significantly smaller increase in their rectal temperature during 55% maximal exercise for 60 min in heat (32 °C 70% relative humidity), even with a similar sweating and skin blood flow response in Japanese. The better heat tolerance in Malaysians could be explained by the greater convective heat transfer from the body core to the skin due to the greater core-to-skin temperature gradient. In addition, when they were hydrated, Malaysian participants showed better body fluid regulation with smaller reduction in plasma volume at the end of the exercise compared to the non-hydrated condition, whereas Japanese showed no difference between hydration conditions. We further investigated the de-acclimatization of heat adaptation by longitudinal observation on the heat tolerance of international students who had moved from tropical areas to Fukuoka for several years.